ASYLUM SEEKERS IN A NON-IMMIGRANT STATE AND THE ABSENCE OF REGIONAL ASYLUM SEEKERS MECHANISM: A CASE STUDY OF ROHINGYA ASYLUM SEEKERS IN ACEH-INDONESIA AND ASEAN RESPONSE - Dewansyah, Bilal; Dramanda, Wicaksana; Mulyana, Imam (UI Scholars Hub, 2017)
The problem of asylum seekers has become a global humanitarian issue. Demands regarding the handling mechanisms based on the values of human rights is getting stronger voiced by the international community. In the Southeast Asian region, the number of ethnic Rohingya asylum seekers has increased and has started to demand settlement in non-immigrant countries like Indonesia. Although Indonesia does not have international obligations in handling asylum seekers, constitutionally, Indonesia has an obligation to guarantee the right of everyone to obtain asylum which has been included in the Constitution. In a global perspective, humanitarian issues in the handling of asylum seekers has begun to be driven towards the handling model based on regionalism. Therefore, ASEAN’s response to the issue of asylum seekers should start a discourse given the number of asylum seekers in Southeast Asia began to rise. This paper deals with the immigration policy on asylum seekers of Rohingya people in Aceh province of Indonesia who plight in 2015 “boat people crisis” with regionalism approach.